Revision of the genus Macrostomus Wiedemann (Diptera, Empididae, Empidinae). IV. The amazonensis species-group - Rafael, José Albertino; Cumming, Jeffrey M. (Zootaxa, 2015)
Six new species of Macrostomus Wiedemann are described, namely M. acreanus sp. nov. from Brazil (Acre state), M. amazonensis sp. nov. from Guyana and Brazil (Roraima, Amazonas, Pará, Rondônia, and Mato Grosso states), M. albicaudatus sp. nov. from Brazil (Roraima, Amazonas, and Pará states), M. paraiba sp. nov. from Brazil (Paraíba state), M. trombetensis sp. nov. from Brazil (Pará state) and M. xavieri sp. nov. from Guyana and Brazil (Amazonas state). The six species are all treated in the M. amazonensis species-group, which is defined on the basis of one pair of ocellar setae and no supra-alar postsutural setae in combination with characters of the male and female terminalia. A key to the included species is presented and the geographical distributions of the species are mapped.